The Cylindrobulla / Ascobulla complex—unraveling problems in identification and adding to Cylindrobulla diversity (Gastropoda, Heterobranchia, Sacoglossa) by describing a new species - Laetz, Elise; Christa, Gregor; Händeler, Katharina; Wägele, Heike (Zootaxa, 2014)
Sacoglossa (Gastropoda: Heterobranchia) are generally considered a monophyletic group, previously associated within the now defunct “Opisthobranchia”, but now basally located within Panpulmonata. In the light of this new phylogenetic hypothesis, detailed knowledge of the most basal groups within Sacoglossa is of paramount importance. This study focuses on the genus Cylindrobulla, which is usually considered the most basal group within the Sacoglossa from a morphological point of view, because it does not share the typical elongate radula teeth of all other Sacoglossa. We describe a new species, Cylindrobulla schuppi sp. nov., and provide data on its food. We reexamined and clarify the radula of the type species C. beauii, review the genus with all other valid species, provide new characters to aid in the proper identification of species within this genus, compare it to the very similar genus Ascobulla, present a determination key using external characters to ensure proper identification of the two similar genera, and discuss phylogenetic relationships within the shelled sacoglossan, the Oxynoacea.